2021
DOI: 10.31820/pt.30.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Attributions and Emotions Associated With Willingness to Help and Government Aid

Abstract: This study aims to understand how willingness to help people in poverty and the agreement with providing government aid are connected to emotions and attributional processes, in a country with a high poverty rate such as Argentina. Differences in poverty attributions and emotions among self-reported social class are also analysed. A total sample of 331 secondary-school students completed self-administered questionnaires. Correlations and regression analyses showed that, whereas emotions such as compassion, emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
2
9
1
2
Order By: Relevance
“…In the latter study, the largest number of participants attributed the causes of homelessness to structural, intrinsic and health-related factors, which is also in line with our research. These findings con-firm numerous earlier studies on poverty attributions, where it was shown that those citizens who believe that the causes of poverty are primarily related to the responsibility of the broader social environment show greater sensitivity and perceive people living in poverty more positively (Appelbaum, 2001;Henry et al, 2004;Yúdica et al, 2021). However, Vasquez et al (2016 point out that attributing the causes of homelessness to individualistic factors, with the consequent attribution of responsibility for one's situation to individuals, can have the opposite effect, namely the perception of the general population that homeless people may not deserve help.…”
Section: Discussionsupporting
confidence: 86%
“…In the latter study, the largest number of participants attributed the causes of homelessness to structural, intrinsic and health-related factors, which is also in line with our research. These findings con-firm numerous earlier studies on poverty attributions, where it was shown that those citizens who believe that the causes of poverty are primarily related to the responsibility of the broader social environment show greater sensitivity and perceive people living in poverty more positively (Appelbaum, 2001;Henry et al, 2004;Yúdica et al, 2021). However, Vasquez et al (2016 point out that attributing the causes of homelessness to individualistic factors, with the consequent attribution of responsibility for one's situation to individuals, can have the opposite effect, namely the perception of the general population that homeless people may not deserve help.…”
Section: Discussionsupporting
confidence: 86%
“…A pesar de que existen diversos estudios sobre las atribuciones causales de la pobreza, la mayoría han sido implementados en Estados Unidos y países de Europa, y muy pocos fueron desarrollados en África (e. g., Baguma y Furnham, 2012), Asia (e. g., Halik y Webley, 2011) y América Latina (e. g., Bastias et al, 2019;Gatica et al, 2017;Reyna y Reparaz, 2014;Yúdica et al, 2021). La falta de estudios en regiones caracterizadas por mayores tasas de pobreza e inequidad resulta relevante dado que las opiniones y percepciones de las personas sobre las causas de la pobreza estarían influenciadas por las experiencias vividas y aspectos culturales (Da Costa y Dias, 2015; Pirani, 2013).…”
Section: Introductionunclassified
“…Despite contradicting the selfinterest logic, it aligns with the enlightening effect of education (Kreidl, 2000). The effect of socioeconomic status in terms of the household assets confirms the self-interest theory, as possessing more household assets is associated with a stronger propensity for individual blame and with less support of social fate as an explanation for poverty (Svallfors, 2002;Yúdica et al, 2021;Özpinar and Akdede, 2022). Ethnicity is an important predictor: Indo-Guyanese are more likely to blame the individual and less likely to attribute poverty to the social structure.…”
Section: Predicting Poverty Attributionsmentioning
confidence: 70%
“…Early work has considered self-interest as a main driver for individual's positions towards poverty (Furnham, 1982(Furnham, , 1983Payne and Furnham, 1985;Kluegel and Smith, 1986;Hayati and Karami, 2005). Economically disadvantaged groups (women, minorities, working class, lower educated, and lower incomes) are expected to be more likely to ascribe poverty to structural inequalities instead of individual characteristics whereas economically advantaged groups (men, whites, middle/higher classes, higher educated, and higher incomes) should explain poverty in more individualistic terms (Hunt, 1996;Cozzarelli et al, 2001;Nasser et al, 2002;Svallfors, 2002;Yúdica et al, 2021). These relations have mostly been explained by self-interest theory (Form and Hanson, 1985;Hasenfeld and Rafferty, 1989;Hunt, 1996), which holds that individuals will favour explanations that legitimise their welfare state (in) dependence.…”
Section: Explanations Of Poverty Attributionsmentioning
confidence: 99%